Memory and thinking problems that aging Latinos in New York City would bring to a doctor’s attention - Karolynn Siegel; María Cabán; Evelyn Tran; Alicia Meng; John B. Wetmore; Ruth Ottman (PLoS ONE, 2026)
The number of individuals with Alzheimer’s disease will grow dramatically in the coming decades. Early diagnosis benefits patients, caregivers and society, but depends heavily on afflicted individuals or their family members recognizing early symptoms as possible indications of a medical problem and seeking medical care. To examine the kinds of memory or thinking problems, Latinos ages 40–64 would seek medical care for, we analyzed data from 161 participants in a community-based study in northern Manhattan of the impact of receiving information about one’s risk of developing late-onset Alzheimer’s disease. Participants were asked whether experiencing each of 5 different memory or thinking problems multiple times over 2–3 months would make them seek medical care. Participants often offer a benign or normalizing attributions for symptoms. Disorientation was the most frequently endorsed problem. Considerations found to be associated with an inclination or disinclination to want to see a doctor about a symptom were identified. A better understanding of what Latinos would consider in deciding whether or not to bring different memory problems to a doctor’s attention can help guide the development of educational interventions to encourage help-seeking and facilitate earlier diagnosis.